Perancangan Desain Aplikasi “Tulisan-Ku” Menggunakan Metode Design Thinking Dan Heuristic Evaluation - Christhoper Fernado Cias; I Made Ardwi Pradnyana; Putu Yudia Pratiwi (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2026)
Digital technology development provides opportunities for writers and readers to access and publish literary works more widely. However, several similar applications still have limitations in writing feature flexibility, ease of use, and opportunities for writers to generate income from published works. This study aims to design the Tulisan-ku application as a platform for writers and readers by emphasizing usability, creativity support, and an appreciation system for writers.The method used in this study is Design Thinking, which consists of the empathize, define, ideate, prototype, and testing stages. The empathize stage was conducted through interviews with potential writer and reader users to identify user needs and problems. The analysis results were then translated into user personas, feature formulation, and prototype design using Figma. The testing stage was carried out using Heuristic Evaluation based on Nielsen’s ten usability principles.The results of the study indicate that the application prototype was successfully designed with main features including story writing, content publication, user communities, a donation system for writers, and social interaction features among users. The evaluation results show that the prototype design fulfilled most usability principles, although several aspects still require further improvement. Therefore, the Tulisan-ku application is expected to become a digital solution that supports the ecosystem of writers and readers more effectively. The evaluation also showed that the prototype achieved a good usability score, with average ratings ranging from 4.3 to 4.6.